2018
DOI: 10.1155/2018/7682098
|View full text |Cite
|
Sign up to set email alerts
|

A Formula Adaptive Pixel Pair Matching Steganography Algorithm

Abstract: Pixel pair matching (PPM) is widely used in digital image steganography. As an important derivation, adaptive pixel pair matching method (APPM) offers low distortion and allows embedded digits in any notational system. However, APPM needs additional space to store, calculate, and query neighborhood set, which needs extra cost. To solve these problems, a formula adaptive pixel pair matching (FAPPM) method is proposed in this paper. The basic idea of FAPPM is to use the formula to get the stego image pixel pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The test results demonstrated that the proposed strategy enhances the text retrieval at a lower error rate of execution of the C1BT-BME, 1BT-BME, MF-1BT, and it outperforms other low bit-depth based text retrieval [19] techniques at the MB level. The Adaptive Block Matching Steganography Algorithm Using Bit-Plane Matching considers the magnitude as well as the directive data of the pixel elements in the MB [20].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results demonstrated that the proposed strategy enhances the text retrieval at a lower error rate of execution of the C1BT-BME, 1BT-BME, MF-1BT, and it outperforms other low bit-depth based text retrieval [19] techniques at the MB level. The Adaptive Block Matching Steganography Algorithm Using Bit-Plane Matching considers the magnitude as well as the directive data of the pixel elements in the MB [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The function of the normalized phase correlation of X c K 1 ; K 2 ð Þand X p K 1 ; K 2 ð Þis defined in Eq. (20).…”
Section: Mve 1 Mvementioning
confidence: 99%
“…Often statistical analyses can easily detect the pattern of the altered pixels as shown in (Fridrich, Goljan, and Du 2001;Lerch-Hostalot and Megías 2016;Luo, Huang, and Huang 2010). Recent works have therefore focused on methods that preserve the original image statistics or the design of sophisticated distortion functions (Holub and Fridrich 2012;Holub, Fridrich, and Denemark 2014;Long and Li 2018;Pevnỳ, Filler, and Bas 2010;Swain 2018;Tamimi, Abdalla, and Al-Allaf 2013).…”
Section: Related Workmentioning
confidence: 99%